If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2x + 4 = 2 + x + 2 Reorder the terms: 4 + 3x + -2x = 2 + x + 2 Combine like terms: 3x + -2x = 1x 4 + 1x = 2 + x + 2 Reorder the terms: 4 + 1x = 2 + 2 + x Combine like terms: 2 + 2 = 4 4 + 1x = 4 + x Add '-4' to each side of the equation. 4 + -4 + 1x = 4 + -4 + x Combine like terms: 4 + -4 = 0 0 + 1x = 4 + -4 + x 1x = 4 + -4 + x Combine like terms: 4 + -4 = 0 1x = 0 + x 1x = x Solving 1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1x + -1x = x + -1x Combine like terms: 1x + -1x = 0 0 = x + -1x Combine like terms: x + -1x = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| 2.5(2x+5)=5(x+2.5) | | -3(n-4)-27=17 | | v-5=7+5(8-5v) | | 6(-4+2x)=-132 | | 11-8x=3(1-3x) | | m^2-20=0 | | 12x^2-38x-12=0 | | 4g-3g=1+g | | -18-4n=-7(2n-6) | | -8x-40=4(-4x-6) | | 16x^6y^10=0 | | 10+15y=75y-2 | | -7(3b-7)=-2b+30 | | 8x^2-2x+4=0 | | [5x-2]=12 | | 8x-6+10x-12=180 | | 8x^2-2x+4=y | | 2m^2-13m+6=0 | | 4(x-4)=5-3x | | x+17=3x-35 | | 11=17-2b | | -33+6b=-(b-2) | | x+9=3x-37 | | 8034*n=80.34 | | 0.5d-0.83d=4 | | 8(7x-1)=64 | | 3x-9=6x+36 | | 4x=(23x+18) | | 12x^2-200=0 | | 14-2x=-5x | | m+4=6.7 | | 3x-11=x+3 |